AN ANALYSIS OF LEXICAL SEMANTIC MEANING IN ALBUM “LOVER” BY TAYLOR SWIFT - Zulaikah Zulaikah; Nurul Hasanah; Dwi Astuti; Endang Komsatun (PROJECT (Professional Journal of English Education), 2024)
Language serves as a medium for communicating messages, whether through spoken or written means. An in-depth analysis of the meaning of words, phrases, and a sentences is crucial as it enhances the clarity of communication and allows for different perspectives on semantics. The term "song" typically refers to a form of literary expression that encompasses various types of creative writing, such as poetry, theatre, fiction, nonfiction, journalism, and songwriting. This study involves the analysis of literary works, such as songs. The writer selects four tracks from Taylor Swift's album "Lover": "Lover," "Daylight," "Cruel Summer," and "London Boy." The writers selected these songs because to their intriguing nature, which warrants more examination and in-depth analysis. This study employed a descriptive qualitative technique. The investigation yielded 12 data points that have both lexical and contextual significance.